Sierra Leone - Public Expenditure Review : From Post-Conflict Recovery to Sustained Growth - World Bank (Washington, DC, 2013)
This Public Expenditure Review is to assist the Government of Sierra Leone in repositioning itself for sustained growth and poverty reduction in the long-run as opposed to the short-term expediencies needed during the present post-conflict phase. The report focuses on the period 2001-2003 for history and 2004-2006 for the future. A review of older historical data at the aggregate level is done in the macroeconomic section for the period 1998-2003 in order to demonstrate the contrast between the war and post-war years. The report covers the fiscal policies of Government in aggregate and goes deeper for three sectors: security, agriculture and education. All three are critical to growth and poverty reduction. It also proposes a number of changes in the budget process. It reviews the budgets and capacity of the security service ministries, departments and agencies (MDAs). The maintenance of security is fundamental: without it, there is little incentive to invest for future growth. The report examines the budgets and capacities of the agricultural MDAs. Finding ways to increase agricultural growth is equally critical, especially since the majority of the population still lives in rural areas. The education sector is also examined in depth, due to its central contributions to the long-run productivity of the workforce - and because of its large impact on the fiscal stance of Government.